Pelaksanaan Pilkada Serentak: Tinjauan Hukum Tata Negara dan Dampaknya Terhadap Demokrasi di Indonesia - Riastri Haryani (CV. Social Politic Genius (SIGn), 2023)
This study aims to examine and analyze the execution of Simultaneous Local Elections within the study of constitutional law and its impact on democracy in Indonesia. This study uses normative legal research with the statute and conceptual approaches. The collected legal material is then qualitatively analyzed to describe the problem and answer study purposes. The results show that implementing the 2024 Simultaneous Local Elections presents some crucial impacts on the Local Elections held in 2017, 2018, and 2020. The first impact, related to the 2017 and 2018 Local Elections, involves the ASN as Interim Regional Heads during the transition toward the 2024 Simultaneous Local Elections. However, this provision reflects principles of accountability and continuity of government, which are also critical parts of a democratic system. The second impact, particularly for the 2020 Local Elections, reduces the Regional Head’s term, initially set to serve until 2026. In contrast, legal considerations in Decision Number 18/PUU-XX/2022 decided that reducing the term of Regional Head due to the 2024 Simultaneous Local Elections does not contradict the 1945 Constitution. Therefore, several recommendations can be formulated for relevant parties. First, the appointment process of Interim Regional Heads should be more transparent and involve public consultation where possible. Second, serious consideration should be given to the impact of reduced terms for Regional Heads elected in 2020. Mechanisms should be in place to ensure that the reduction does not adversely affect the quality of governance or disrupt ongoing projects. Finally, the consideration in Decision Number 18/PUU-XX/2022 and the 1945 Constitution should guide all decision-making processes related to the 2024 Simultaneous Local Elections. Thus, a careful, balanced approach is needed in the execution of the 2024 Simultaneous Local Elections to maintain democratic integrity, the rule of law, and public trust.